Diagnostic challenges of rarely well-differentiated adenocarcinoma of the stomach - Tian Qin; Tian Qin; Yong Wang; Zebin Xiao; Lili Ma; Chao Fan; Chongyu Zhu; Luqiao Luo; Qingling Zhang; Chao Liu (Pathology and Oncology Research)
BackgroundFundic gland tumors are a rare subtype of gastric tumors with fundic gland differentiation. This group of tumors has a low incidence rate and shows indistinctive cellular atypia, obvious structural atypia, special tissue morphology, and clinical prognosis, thus leading to diagnostic challenges.AimWe aimed to investigate the clinical and endoscopic characteristics and pathological features of gastric adenocarcinoma of the fundic gland (GA-FG) to provide a better understanding of this disease.MethodsWe collected data from patients diagnosed as having GA-FG at Guangdong Provincial People’s Hospital between January 2019 and April 2024. The analysis focused on their clinical data, endoscopic characteristics, pathological morphological characteristics, immunohistochemistry results, treatment, and prognosis.ResultsAmong the four patients were two men and two women (age range, 52–65 years). The tumors were mainly located in the gastric fundus and gastric body, and the lesions commonly had a superficial bulge. Three patients had an initial diagnosis of oxyntic gland adenoma, which was diagnosed as GA-FG after complete resection. These tumors were negative for MUC5AC, but showed diffuse strong positivity for MUC6 and pepsinogen I, and synaptophysin expression.ConclusionGA-FG is a rare gastric tumor with unique morphological features. As it is difficult to diagnose with a biopsy, immunohistochemistry plays an important role in the differential diagnosis. Oxyntic gland adenoma can be regarded as the intramucosal stage of GA-FG. Although all patients were negative for MUC5AC expression, MUC6 and pepsinogen I can help the diagnosis of GA-FG.